Internal Structure Test of Big Five Inventory - Sutejo, Agus; Siaputra, Ide Bagus; Lasmono, Hari K. (Faculty of Psychology, Universitas Surabaya, 2011)
The purpose of this study was to explain the internal structure of Big Five personality trait instrument, namely the Big Five Inventory (BFI). Maximum likelihood method of factor analysis in SPSS 16.0 was used to find suitability between the model proposed and data collected. Subjects (N=156) were all psychology students. Results reveal that five factors personality (Big Five) as proposed by personality theory is not in accordance with data collect- ed. Seven factor model is more appropriate to explain personality, namely openness to ex- perience, conscientiousness, friendliness, introversion, emotional stability, aggressiveness, and vulnerability. The findings have two alternative meanings, first an essential difference in meaning derived from the translated instrument items that could exhibit different responses, and second, the large spectrum of personality characteristics in